CLINICAL ECONOMY EFFICACY OF TARGETED APPROACH TO ACUTE CORONARY SYNDROME PATIENTS MANAGEMENT WITH PERCUTANEOUS INTERVENTION - L. V. Shukil; О. Yu. Korennova; S. P. Podolnaya; E. P. Prikhodko (Российский кардиологический журнал)
Aim. Clinical economical grounding of necessity for continuation of a “State Managed Program of Omsk Region “Development of Healthcare in Omsk Region” (the Program) in allowance granted supply with life saving medications of patients after endovascular treatment of acute coronary syndrome.Material and methods. To the study, by a continuous sampling method, 255 patients included, after endovascular treatment of coronary arteries in acute coronary syndrome during July 1 to December 31 2015, who monthly attended cardiologists office and received free acetylsalicylic acid, clopidogrel and atorvastatin for 12 months. Method of clinical and economical analysis was applied “Increment efficacy of expenses”, and a threshold for self-payment by patients was evaluated.Results. One-year mortality of the Program participants was 1,2% versus 3,5% in non-participants. Hospitalization rate for repeated acute coronary syndrome was 3,5% versus 9% in non-participants; serious adverse event hospitalization rate was less than 1%. All economically active patients were discharged “to work”.Calculated parameter of increment efficacy of expenses with the technology “stenting of coronary arteries and drug supply in 2018 (statin, acetylsalicylic acid, clopidogrel or ticagrelor)” was 215906,93 Rub for every additional survived patient with no hospitalizations for repeated acute coronary syndrome during one year after stenting.Conclusion. Technology of medication supply with life saving drugs of patients underwent endovascular interventions on coronary arteries for acute coronary syndrome is an advantageous investment of budget funds to life quality of patients. The results of the analysis have grounded the necessity to continue program targeted method in acute coronary syndrome patients management after percutaneous intervention taken current clinical guidelines.